Da’wah Bil Hal and Muslim Women’s Religious Humanist Ideology in Indonesian Film - Gusti Anggraini, Rizka; Rubino, Rubino; Yusriani Simamora, Irma (MUHARRIK: Jurnal Dakwah dan Sosial, 2022)
This study aims to find out the overview of da'wah bil hal as an approach for proselytizing through actual actions or the role model from attitudes and behaviours represented in the religious film entitled "Merindu Cahaya de Amstel" by Hadrah Daeng Ratu. This research used the descriptive-analytic method to analyze the meaning of data in a movie using John Fiske's semiotic theory, which involve three levels, namely reality, including (1) appearance, costumes, environment, manner of speaking, gestures, and facial expressions; (2) representation, including, conflict, action and dialogue; and (3) ideology, the interpretations result of the fundamental level and representations categorized in social relations by ideological codes. The results showed that the da’wah bil hal approach in the movie "Merindu Cahaya de Amstel" was depicted through the appearance of the main character named Khadija, seen in her closed clothes (aurat). Besides, the way of speaking, gestures, and facial expressions revealed the personality of Muslims who are polite, helpful and have good respect for others. How Khadija's conflicts, actions, and dialogues are represented in this movie shows the characteristics of Muslims with a good character, balancing hablumminallah and hablumminannas, patience, devout worship, and always spreading usefulness. The practice of da'wah bil hal or proselytizing through the figure of Khadija, showed an ideology of religious humanism. The novelty of this research is the analysis of da’wah bil hal in a movie through the depiction of Muslim female characters applying Islamic values, including morals, trust, and worship.